Taurine Alleviates Streptococcus uberis-Induced Inflammation by Activating Autophagy in Mammary Epithelial Cells - Wang, Zhenglei; Lan, Riguo; Xu, Yuanyuan; Zuo, Jiakun; Han, Xiangan; Phouthapane, Vanhnaseng; Luo, Zhenhua; Miao, Jinfeng (Frontiers in Immunology, 2021)
Streptococcus uberis infection can cause serious inflammation and damage to mammary epithelial cells and tissues that can be significantly alleviated by taurine. Autophagy plays an important role in regulating immunity and clearing invasive pathogens and may be regulated by taurine. However, the relationships between taurine, autophagy, and S. uberis infection remain unclear. Herein, we demonstrate that taurine augments PTEN activity and inhibits Akt/mTOR signaling, which decreases phosphorylation of ULK1 and ATG13 by mTOR and activates autophagy. Activating autophagy accelerates the degradation of intracellular S. uberis, reduces intracellular bacterial load, inhibits over-activation of the NF-κB pathway, and alleviates the inflammation and damage caused by S. uberis infection. This study increases our understanding of the mechanism through which taurine regulates autophagy and is the first to demonstrate the role of autophagy in S. uberis infected MAC-T cells. Our study also provides a theoretical basis for employing nutritional elements (taurine) to regulate innate immunity and control S. uberis infection. It also provides theoretical support for the development of prophylactic strategies for this important pathogen.